2011
DOI: 10.1002/hup.1213
|View full text |Cite
|
Sign up to set email alerts
|

The low frequency of reported sexual dysfunction in Asian patients with schizophrenia (2001-2009): low occurrence or ignored side effect?

Abstract: The results of this study indicate that SD was seldom recorded as a side effect by Asian psychiatrists while treating patients with schizophrenia. It is unclear whether the low prevalence of reported SD compared with Western data is real or whether the results are being insufficiently recognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Cultural/religious differences may influence sexual behavior and therefore the rate of SD in both general populations and SZ (Hocaoglu et al, 2014). The absence of validated questionnaire may explain some results with very low rate (until 3%) of SD in some studies (Xiang et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…Cultural/religious differences may influence sexual behavior and therefore the rate of SD in both general populations and SZ (Hocaoglu et al, 2014). The absence of validated questionnaire may explain some results with very low rate (until 3%) of SD in some studies (Xiang et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, patient reports of sexual dysfunction are significantly influenced by cultural factors and social acceptance in discussing sexual issues. According to a meta analysis, the prevalence of sexual dysfunction reported in Asia countries was lower than western counties [15]. Further, clinicians themselves may be conservative in enquiring about sexual concerns or consider sexual-related complains as insignificant in schizophrenia patients as compared to positive psychotic symptoms [17].…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life is increasingly used to assess treatment outcome for schizophrenia patients [12, 19, 50, 51], and sexual function is an important part of QoL, which could be influenced by social-demographic characteristics [19], psychopathology [12], treatment modalities (eg, antipsychotic drugs) [5254] and side effects [15, 55]. One study reported that patients with schizophrenia were more dissatisfied with their sex life than any other aspects of life [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Talking about sex can make subjects feel shame, and reporting sexual dysfunction can damage their selfesteem. Therefore, people in Asia, especially in rural areas, are more likely to underestimate their sexual dysfunction (6,44). In addition, age is another important risk factor for sexual dysfunction in the general population (45) and schizophrenia patients (15,38).…”
Section: Discussionmentioning
confidence: 99%